Help‐seeking behaviour of patients with haematological malignancies treated with autologous stem cell transplantation. (3rd February 2016) - Braamse, A.M.J.; van Meijel, B.; Visser, O.J.; Huijgens, P.C.; Beekman, A.T.F.; Dekker, J.
Abstract : Patients with haematological malignancies undergoing autologous stem cell transplantation face a life‐threatening illness and stressful treatment. Although many patients report problems, relatively few patients report a need for additional professional care after treatment. We aimed to gain insight into the factors underlying this discrepancy by exploring patients' needs and help‐seeking behaviour in relation to their experienced symptoms and problems. A qualitative research design following the grounded theory approach was used. Twenty patients, treated with autologous stem cell transplantation in the past 2 years, participated in an individual semi‐structured interview. Factors contributing to patients' help‐seeking behaviour were derived from our data and ordered in the following categories: (1) transition from symptoms to problems; (2) preference for dealing with problems themselves and with help from relatives; (3) problem categories and coping strategies; and (4) motives for (not) bringing in professional help. We concluded that the mere presence of a symptom does not lead to help‐seeking behaviour: this relationship is modified by patients' personal goals, future perspective and phase of recovery. Patients seem to prefer to deal with problems without professional care. Patients' actual appeal for professional care depends on their coping strategies, social network and knowledge of available care.